Memperkuat Peran Pemerintah Daerah: Mengelola Pariwisata Lokal Yang Berkelanjutan - Sentanu, I Gede Eko Putra Sri; Mahadiansar, Mahadiansar (Jurnal Ilmu Administrasi Negara (JUAN), 2020)
Tourism governance will have an impact on the environment, which is controlled by local governments. The development of the tourism sector is essential to improve the welfare of the community and the regional economy. Strengthening the role of local government as a leading tourism sector in the region is considered to be able to encourage the creation of a collaboration between industries (actors) to manage sustainable local tourism. This paper was written to find out how far the role of local government is and how relations between sectors (actors) are in managing sustainable regional tourism. This study uses a literature study approach, with documentation data collection techniques derived from the study of several reputable journals, books, and other secondary sources that are relevant to this research. The data analysis technique is content analysis. In tourism management, the role is not only done by one party but all supporting aspects and involved in the framework of creating orchestration and ensuring the quality of activities, facilities, services, and to create experiences and value of tourism benefits to provide benefits to the community and the environment. These will be able to encourage the tourism system through the optimization of roles and collaboration between business, government, society, academics, and media.